Conurbations and resilience. When growth makes us fragile - Cutini, Valerio (TeMA - Journal of Land Use, Mobility and Environment, 2017)
This paper is focused on the conurbations, extensive urban areas resulting from the expansion and coalescence of several neighbouring cities. Two theses underlay the research. The first is that, in the development of a conurbation, traffic has actually a role of ‘maker and breaker of cities’, just to paraphrase the title of a well-known article by Colin Clark, focusing on the double role of roads and traffic in urban development (Clark, 1958): on a one hand, the making of a unique road network, encompassing the whole grid, actually allows movement and interaction all over the settlement, making possible the working of the conurbation as a wide urban system; on the other hand, the resulting pattern of movement concentrates its major flows on few roads connecting the original nuclei and the new development areas, actually bypassing the pre-existing urban fabric and diverting a significant amount of local traffic from the streets of the urban grid, what involves the loss of the fertilisation benefit the irrigation of through movement provides. The second thesis, complementary to the former, is that the merging of the nuclei and their embedding into a conurbation reduces the resilience of the whole settlement, in that it affects the capability of the system to adsorb accidental events and transformations without significantly changing its global behaviour. The phenomenon of conurbations and the diachronic analysis of their resilience will here be observed from a configurational point of view, analysing by means of space syntax techniques the urban settlement of Florence, here assumed as an ideal case study. The results are expected to objectively describe the role of inter-urban roads in the making of a conurbation, and to appraise the extent to which their entanglement within the whole concur in transforming its inner geography and enhancing its global vulnerability. More in general, the configurational approach, suitable for appraising the urban grid as the interface between the physical city and the phenomena that occur along its paths, once again proves its usefulness in linking spatial issues and traffic questions, so as to bridge the traditional gap between urban design, focused on the morphologic features of blocks and buildings, and transport analysis, strictly concerned with the distribution of movement flows on the streets network.